Review: The distribution, flow, and quality of Grand Canyon Springs, Arizona (USA) - Tobin, Benjamin W.; Springer, Abraham E.; Kreamer, David K.; Schenk, Edward (Hydrogeology journal, 2018)
An understanding of the hydrogeology of Grand Canyon National Park (GRCA) in northern Arizona, USA, is critical for future resource protection. The ~750 springs in GRCA provide both perennial and seasonal flow to numerous desert streams, drinking water to wildlife and visitors in an otherwise arid environment, and habitat for rare, endemic and threatened species. Spring behavior and flow patterns represent local and regional patterns in aquifer recharge, reflect the geologic structure and stratigraphy, and are indicators of the overall biotic health of the canyon. These springs, however, are subject to pressures from water supply development, changes in recharge from forest fires and other land management activities, and potential contamination. Roaring Springs is the sole water supply for residents and visitors (>6 million/year), and all springs support valuable riparian habitats with very high species diversity. Most springs flow from the karstic Redwall-Muav aquifer and show seasonal patterns in flow and water chemistry indicative of variable aquifer porosities, including conduit flow. They have Ca/Mg-HCO 3 dominated chemistry and trace elements consistent with nearby deep wells drilled into the Redwall-Muav aquifer. Tracer techniques and water-age dating indicate a wide range of residence times for many springs, supporting the concept of multiple porosities. A perched aquifer produces small springs which issue from the contacts between sandstone and shale units, with variable groundwater residence times. Stable isotope data suggest both an elevational and seasonal difference in recharge between North and South Rim springs. This review highlights the complex nature of the groundwater system.